2017
DOI: 10.4049/jimmunol.1700256
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Dynamics in Rhesus Macaques Infected with a Brazilian Strain of Zika Virus

Abstract: Zika virus (ZIKV) is a mosquito-borne and sexually transmitted flavivirus, associated with fetal CNS-damaging malformations during pregnancy in humans. This study documents the viral kinetics, and immune responses in rhesus macaques infected with a clinical ZIKV Brazilian isolate. We evaluated the viral kinetics and immune responses induced after an i.v. infection with a Brazilian ZIKV clinical isolate (HS-2015-BA-01) in rhesus macaques for up to 142 days. ZIKV-specific antibody-secreting cells (ASCs), germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 54 publications
2
44
0
1
Order By: Relevance
“…Additionally, depletion of CD8 T cells results in higher viremia in mice . However, despite this evidence of T‐cell response to ZIKV infection in mice, in rhesus macaques populations of CD8+ T cell subsets remain mostly stable during the course of infection …”
Section: Modeling Immune Control Of Viremiamentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, depletion of CD8 T cells results in higher viremia in mice . However, despite this evidence of T‐cell response to ZIKV infection in mice, in rhesus macaques populations of CD8+ T cell subsets remain mostly stable during the course of infection …”
Section: Modeling Immune Control Of Viremiamentioning
confidence: 99%
“…There has also been much effort directed toward understanding the generation and protective capacity of anti-ZIKV antibodies, as reviewed in Priyamvada et al 83 In macaque models, after a high-dose intravenous infection, total numbers of B cells increased on day 3, while antigen-specific IgG titers were not detectable until well after clearance of the plasma virus, suggesting that the antibody response was more important for long-term protection than short-term control. 84 The long-term protective role of antibodies in ZIKV infection is supported by work from a number of groups. 85,86 Aliota et al 85 found that rhesus macaques were protected from secondary homologous and heterologous challenge 70 days after primary infection.…”
Section: Adaptive Immune Responses and Antibodymediated Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-human primates (NHPs) are the best documented animal reservoirs for ZIKV (and related flaviviruses). ZIKV infection has been achieved in male, and non-pregnant and pregnant female rhesus (Macacca mulatta) (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) cynomolgus (Macacca fascicularis) (22,32) and pigtail macaques (Macacca nemestrina) (33) following subcutaneous (SC) inoculation with French Polynesian (H/PF/2013), (20) Puerto Rican (PRVABC59, 2015) (21,22,(30)(31)(32), Brazilian (Brazil/ZKV2015; Zika virus/H.sapiens-tc/BRA/2015/Brazil_SPH2015) (26)(27)(28)(29) and Cambodian strains of ZIKV (FSS13025) (32). There are now several reports of ZIKV infection in pregnant macaques, with one study describing infection of a single pigtail macaque using an Asian strain (FSS13025 strain; Cambodia, 2010) (33), and four studies with pregnant rhesus macaques infected with either the French Polynesian or Puerto Rican strains (20,23,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…In a study on "Rhesus Macaques Infected with a Brazilian Strain of Zika Virus" Silveira by et al, "lymph node hyperplasia was clearly visible postviremia but was associated with low frequencies of ZIKV-specific Ab-secreting cells in lymph nodes and bone marrow [5]." In non-human primate, the Zika virus is proved for existence in lymph node [6].…”
mentioning
confidence: 99%